2020
DOI: 10.7759/cureus.7871
|View full text |Cite
|
Sign up to set email alerts
|

Brodie’s Abscess Masquerading as Vaso-occlusive Crisis in a Sickle-cell Disease Patient

Abstract: Brodie's abscess is a rare form of subacute osteomyelitis, most commonly found in children between the ages of two to fifteen years. It has slight preponderance for males. It is characterised by centrally placed, well-circumscribed abscess within the medulla or metaphysis of long bone, most commonly tibia, surrounded by a sclerotic wall. It is sometimes considered a transitional phase for the development of chronic osteomyelitis due to infection persisting between two to six months without showing any systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, this has to be done after complete eradication of the infection. 1 , 4 As the thickened sclerotic margin of the Brodies abscess can limit the infection from spreading into the bone stream, the systemic symptoms might be delayed or absent, which can be confused with a vaso-occlusive crisis. 1 Although uncommon in sickle cell patients, there are a few reports in the literature for Brodie’s abscess identified in sickle cell patients and only a couple of reports of Brodie’s abscess initially thought to be an acute sick cell crisis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this has to be done after complete eradication of the infection. 1 , 4 As the thickened sclerotic margin of the Brodies abscess can limit the infection from spreading into the bone stream, the systemic symptoms might be delayed or absent, which can be confused with a vaso-occlusive crisis. 1 Although uncommon in sickle cell patients, there are a few reports in the literature for Brodie’s abscess identified in sickle cell patients and only a couple of reports of Brodie’s abscess initially thought to be an acute sick cell crisis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 As the thickened sclerotic margin of the Brodies abscess can limit the infection from spreading into the bone stream, the systemic symptoms might be delayed or absent, which can be confused with a vaso-occlusive crisis. 1 Although uncommon in sickle cell patients, there are a few reports in the literature for Brodie’s abscess identified in sickle cell patients and only a couple of reports of Brodie’s abscess initially thought to be an acute sick cell crisis. 11 A recent systematic review of reported cases in 2019 notes that publications of Brodie’s abscess are predominantly from developed countries 12 ; this may represent a deficiency in the reporting of instances of Brodie’s abscess among developing countries where sickle cell disease is more prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with sickle cell anaemia often present with bone pain and vascular complications, which can obscure the symptoms of coexisting musculoskeletal conditions. The diagnostic difficulty is exacerbated by overlapping clinical symptoms and radiologic findings, requiring a high level of suspicion and a thorough diagnostic assessment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%